The use of carbonate apatite bioglass cement as pulp capping material examined from reparative dentin - Indah Puti Rahmayani Sabirin; Myrna Nurlatifah Zakaria (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
Root canal infection potentially develops to periapical infection as a result of opening of pulp chamber as a pathway for irritants to periapical area. Proper pulp capping procedure can be done to prevent root canal infection by preserving the vitality of the pulp and inducing reparative dentin. Generally, calcium hydroxide (Ca(OH2)) is used as pulp capping material although it stil3Ap) and CO3Ap bioglass cement are bioceramic materials proven for their ability to form new bone structure upon a research on bone tissue. These materials have better mechanical strength than Ca(OH2) and have the ability to set in humid environment similar to the body’s physiological condition. This study was a preclinical trial of CO3Ap and CO3Ap bioglass cement as pulp capping material. The materials were applied on a perforation site of 24 Wistar rat teeth, divided into 4 groups of different treatments, negative control (no treatment), positive control (Ca(OH2)), CO3Ap, and CO3Ap bioglass, respectively. Following the application of the pulp capping materials, the perforation sites were covered with light-cured glass ionomer cement. Evaluation of reparative dentin was performed after 21 days, where the rats were euthanized, and histopathological specimens were stained using hematoxylin and eosin. The results of the study revealed that dentinal bridge was formed on all the treatment and positive control groups (p=0.000) but not on the negative control. We concluded that CO3Ap as well as CO3Ap bioglass cement have the ability to induce the formation of reparative dentin, therefore both materials can be considered as pulp capping material for open pulp or thin dentin condition on pulp chamber roof.